KIFC3 Promotes Proliferation, Migration, and Invasion in Colorectal Cancer via PI3K/AKT/mTOR Signaling Pathway - Liao, Huiling; Zhang, Lan; Lu, Shimin; Li, Wei; Dong, Weiguo (Frontiers in Genetics, 2022)
Background: KIFC3, belongs to kinesin superfamily proteins (KIFs), is well known for its role in intracellular cargo movement. KIFC3 has been identified as a docetaxel resistance gene in breast cancer cells, however, the role of KIFC3 and its potential mechanism in colorectal cancer (CRC) remains elusive. Objectives: We aims to investigate the effects of KIFC3 in proliferation, migration, and invasion in CRC as well as the potential mechanism inside. Methods: We investigated the expression of KIFC3 in the Oncomine, Gene Expression Profiling Interactive Analysis databases. The KIFC3 protein expression and mRNA level in CRC cells were evaluated by western blot and qPCR. Cell proliferation ability was deteceted by CCK-8, EdU, colony formation assay and xenograft tumor in nude mice. Flow cytometry was used to detect the cell cycle arrest. The effect of KIFC3 on the epithelial-to-mesenchymal transition (EMT) was investigated by transwell and wound healing assay. The association of KIFC3 with EMT and PI3K/AKT/mTOR signaling pathways were measured by Western blot and Immunofluorescence Staining. Results: The expression of KIFC3 was higher in CRC tissues than normal colorectal tissue, and was positively correlated with the overall survival of CRC. KIFC3 silencing inhibited the proliferation, migration and invasion of CRC cells. Meanwhile, it could induce cell cycle arrest at the S phase. KIFC3 silencing inhibited the expression of proliferating cell nuclear antigen, p53, Cyclin A2, Cyclin E1, and CDK2 and increased the expression of p21. Additionally, KIFC3 silencing inhibited the EMT process, which decreased the level of N-cadherin, Vimentin, SNAIL 1, TWIST, MMP-2, MMP-9 and increased E-cadherin. Furthermore, the knockdown of KIFC3 suppressed the EMT process by modulating the PI3K/AKT/mTOR signaling pathway. KIFC3 silencing decreased the expression of phosphorylated PI3K, AKT, mTOR, but total PI3K, AKT, mTOR have no change. In a xenograft mouse model, the depletion of KIFC3 suppressed tumour growth. Inversely, the increased expression levels of KIFC3 could enhance the proliferation, migration and invasion of CRC cells, and enhance the EMT process through the PI3K/AKT/mTOR pathway. Conclusion: Our study substantiates that KIFC3 can participate in the regulation of CRC progression by which regulates EMT via the PI3K/AKT/mTOR axis.